Public debt asymmetries: the effect on taxes and spending in the European Union - Signe Krogstrup (European Central Bank (ECB), 2002)
The aim of this paper is two-fold: First, assuming public debts are pre-determined and in their steady state in EU countries, the paper investigates the effect of asymmetric debt service obligations on taxes, primary spending and the tax mix in EU countries. Second, it investigates how increased tax competition may change these effects. The impact of debt service on taxes, primary spending and the tax mix is derived in a simple model of tax competition, and the hypotheses derived from the model are tested empirically for a panel of EU countries. Cross- countrdifferences in public debts are found to lead to asymmetries in taxes and primary expenditures across EU countries, with high debt countries having lower expenditures and higher taxes than low debt countries. Capital mobility is found to increase these asymmetries, and trigger cross-country asymmetries in the tax mix of EU countries.
Keywords: H6; H23; H73; H87; F02; 330